Survivin inhibitor YM155 induces mitochondrial dysfunction, autophagy, DNA damage and apoptosis in Bcl‐xL silenced glioma cell lines. Issue 4 (22nd November 2016) - Jane, Esther P.; Premkumar, Daniel R.; Sutera, Philip A.; Cavaleri, Jonathon M.; Pollack, Ian F.
Abstract : Because the anti‐apoptotic protein Bcl‐xL is overexpressed in glioma, one might expect that inhibiting or silencing this gene would promote tumor cell killing. However, our studies have shown that this approach has limited independent activity, but may tip the balance in favor of apoptosis induction in response to other therapeutic interventions. To address this issue, we performed a pharmacological screen using a panel of signaling inhibitors and chemotherapeutic agents in Bcl‐xL silenced cells. Although limited apoptosis induction was observed with a series of inhibitors for receptor tyrosine kinases, PKC inhibitors, Src family members, JAK/STAT, histone deacetylase, the PI3K/Akt/mTOR pathway, MAP kinase, CDK, heat shock proteins, proteasomal processing, and various conventional chemotherapeutic agents, we observed a dramatic potentiation of apoptosis in Bcl‐xL silenced cells with the survivin inhibitor, YM155. Treatment with YM155 increased the release of cytochrome c, smac/DIABLO and apoptosis inducing‐factor, and promoted loss of mitochondrial membrane potential, activation of Bax, recruitment of LC3‐II to the autophagosomes and apoptosis in Bcl‐xL silenced cells. We also found an additional mechanism for the augmentation of apoptosis due to abrogation of DNA double‐strand break repair mediated by Rad51 repression and enhanced accumulation of γH2AX. In summary, our observations may provide a new insight into the link between Bcl‐xL and survivin inhibition for the development of novel therapies for glioma. © 2016 Wiley Periodicals, Inc.